Harnessing Saussurea lappa for Anti-leishmanial, Anti-toxoplasmic, and Anti-bacterial Activity: Molecular and Computational Insights - Taha, Manal Mohamed Elhassan; Abdelwahab, Siddig Ibrahim; Bharathi, Muruganantham; Koko, Waleed S.; Nasr, Ibrahim S. Al; Khan, Tariq A.; Elmobark, Mohamed Eltaib; Rehman, Zia ur; Moni, Sivakumar S.; Mohan, Syam; Oraibi, Bassem; Alfaifi, Hassan Ahmad; et al. (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives: Saussurea lappa Clark has shown preliminary promise in various biological contexts. This study investigates the antileishmanial, antitoxoplasmic, and antibacterial activities of methanolic extracts from S. lappa roots, focusing on key active components, Dehydrocostuslactone (DHL) and Dihydrodehydrocostus Lactone (DDHL). Materials and Methods: Bioassays were conducted to assess the extract's efficacy against Leishmania major, Toxoplasma gondii, Staphylococcus aureus, and Klebsiella pneumoniae, with cytotoxicity tested on Vero cells using the MTT assay. Molecular docking analyses explored the binding interactions of DHL and DDHL with critical targets, such as pteridine reductase and squalene synthase in L. major; (acyl-carrier-protein) S-malonyltransferase and DNA gyrase in S. pyogenes; and carbapenemase and DNA gyrase in K. pneumoniae. Results: The extract exhibited moderate antileishmanial activity against Leishmania major promastigotes (IC50: 14.7 µg/mL, SI: 1.2) and amastigotes (IC50: 17.2 µg/mL, SI: 1.18), with lower potency compared to Amphotericin B. However, its high toxicity to host macrophages (CC50: 20.3 µg/mL) limits further potential. It showed poor antitoxoplasmal activity (IC50: 14.7 µg/mL, SI: 0.394) and was toxic to Vero cells (CC50: 5.8 µg/mL). Antibacterial assays revealed concentration-dependent inhibition zones against Streptococcus pyogenes (24±1.7 mm at 250 µg/mL) and Klebsiella pneumoniae (37±1.7 mm at 250 µg/mL). Molecular docking showed strong interactions of DHL with Pteridine reductase (-7.1 kcal/mol) and DDHL with Carbapenemase (-7.9 kcal/mol). Both compounds exhibited favorable ADMET profiles, including high oral absorption, suggesting potential as therapeutic agents for further investigation and active compound isolation. Conclusion: These findings highlight the potential of S. lappa as a therapeutic agent and underscore the need for additional preclinical research to further validate and develop its antimicrobial applications.
Keywords: Saussurea lappa; Antimcrobial; Molecular docking; Leishmania major; ADMET